The Association Between Body Mass Index (BMI) and Occupation with the Incidence of Hemorrhoids at Mitra Sejati General Hospital, Medan, in 2023 - Horas Rejeki Manik; Elizabeth Septianur Girsang; Alexander Parlindungan Marpaung; Suryati Sinurat; Harry Butarbuta (Jurnal Kedokteran Methodist, 2025)
Background: Hemorrhoids are a very common anorectal condition defined as symptoms of enlargement and displacement of the normal anal pad to distal. The causes of hemorrhoids themselves are still idiopathic or not widely known, but many are caused by age, gender, lack of drinking and fiber consumption, constipation, occupation, genetics, lack of exercise, overweight, increased intraabdominal pressure. Objective: This study aimed to determine the relationship between body mass index and occupation in hemorrhoid incidence. Methods: This type of study uses an observational analytical method, with a crosssectional design, a data collection method using secondary data obtained from medical records diagnosed with hemorrhoids at Mitra Sejati Hospital, Medan city in 2023. Results: The results of this study showed that there was a relationship between body mass index and the incidence of hemorrhoids with a value of p = 0.024, and there was a significant relationship between work and hemorrhoids with a value of p = 0.031. Conclusion: There is a relationship between body mass index and occupation in hemorrhoid incidence Keywords: hemorrhoids, body mass index, occupationz